2020
DOI: 10.1039/c9py01405e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of light-degradable bromocoumarin functionalized polycarbonates

Abstract: The preparation, characterization and degradation properties of novel light-degradable bromocoumarin functionalized polycarbonates were investigated in the present work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…Preliminary in vitro cellular studies of the above-mentioned nanoparticles and degradation products confirmed that systems have the potential to be used for in vivo studies. Very recently, the same group reported light-degradable APCs nanoparticles by introducing bromocoumarin groups into the side chain [152]. Upon light irradiation, the photo-degradable bromocoumarin side groups are removed, which causes the appearance of nucleophilic amino groups.…”
Section: Light-responsive Apc Nanocarriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary in vitro cellular studies of the above-mentioned nanoparticles and degradation products confirmed that systems have the potential to be used for in vivo studies. Very recently, the same group reported light-degradable APCs nanoparticles by introducing bromocoumarin groups into the side chain [152]. Upon light irradiation, the photo-degradable bromocoumarin side groups are removed, which causes the appearance of nucleophilic amino groups.…”
Section: Light-responsive Apc Nanocarriersmentioning
confidence: 99%
“…Therefore, it would be highly advantageous to use combinations of two or more stimuli to further enhance the tumor-targeted effect, response rate or achieve on-demand burst drug release in tumor site-specific regions. Very recently, the same group reported light-degradable APCs nanoparticles by introducing bromocoumarin groups into the side chain [152]. Upon light irradiation, the photo-degradable bromocoumarin side groups are removed, which causes the appearance of nucleophilic amino groups.…”
Section: Dual/multiple Stimuli-responsive Apc Nanocarriersmentioning
confidence: 99%
“…One reason for this interest is the broad field of possible applications of such polymers, which include catalyst immobilization, sensors, , and patterning , as well as tissue engineering, , drug delivery, and tissue adhesives . Recently, light as a stimulus gained tremendous attention since this trigger can be applied both remotely and accurately by adjusting the parameters of irradiation, such as wavelength, irradiation time, or intensity. , Thus, light-responsive polymers show high potential as efficient and targeted controlled release systems, which reduce side effects compared to conventional therapy. , Photocleavable moieties employed most commonly in such systems are coumarin , and ortho -nitrobenzyl (oNB) derivatives. The combination of different stimuli-responsive units in one polymer is regarded especially useful for controlling release profiles or enhancing release rates of the drug delivery system (DDS). For example, Kalva et al developed a photo and pH dual-responsive polycarbonate (PC) block copolymer conjugated with doxorubicin via an imine linkage to pendant groups that also contain oNB functions .…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Thus, light-responsive polymers show high potential as efficient and targeted controlled release systems, which reduce side effects compared to conventional therapy. 22,23 Photocleavable moieties employed most commonly in such systems are coumarin 24,25 and ortho-nitrobenzyl 26−28 (oNB) derivatives. The combination of different stimuli-responsive units in one polymer is regarded especially useful for controlling release profiles or enhancing release rates of the drug delivery system (DDS).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Besides, when functional groups are incorporated into the polymer backbones; the potential applications will be further broadened. For example, the introduction of hydroxyl, 6–9 carboxyl, 10,11 and amino groups 12–19 can effectively tunning the hydrophilic properties. Pendant functional groups may also provide active sites for further modification such as crosslinking, attaching bioactive substances to satisfy more specific applications 3,4,20,21 .…”
Section: Introductionmentioning
confidence: 99%